2022
DOI: 10.1007/s00481-022-00709-7
|View full text |Cite
|
Sign up to set email alerts
|

Ethikbildung in der Pflege – strukturelle Besonderheiten und didaktische Implikationen der Pflegeausbildung

Abstract: ZusammenfassungDie Pflegeausbildung weist die Besonderheit auf, dass die berufliche Bildung an unterschiedlichen Lernorten erfolgt. Die jeweils beteiligten Lernorte (Lernort Theorie, Lernort Praxis, zunehmend erweitert durch den dritten Lernort, das Skillslab) beeinflussen und fördern die Entwicklung der Ethikkompetenzen der angehenden Pflegfachpersonen – lernortspezifisch als auch lernortübergreifend – in unterschiedlicher Weise. Diese besonderen strukturellen Gegebenheiten des Lehrens und Lernens wirken sich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 54 publications
0
6
0
1
Order By: Relevance
“…What is more, due to its fundamental nature underpinning all aspects and actions of the nursing profession, ethical competency development should be an area of utmost importance within the schools of nursing and it should be supported, addressed and reflected upon cross-sectionally throughout nursing education [ 6 , 24 , 107 ]. While legal regulations solely operate as a foundation for ethics education, Riedel et al [ 8 ] strongly suggested that the comprehensive development of ethical competence was a crucial step in the prevention and professional management of moral distress. Nevertheless, while building ethical competence is an important contribution to preventing and managing moral distress, a higher sensitivity for morally challenging situations simultaneously bears an increased risk for the experience of moral distress if it is impossible to relieve the experienced moral unease.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…What is more, due to its fundamental nature underpinning all aspects and actions of the nursing profession, ethical competency development should be an area of utmost importance within the schools of nursing and it should be supported, addressed and reflected upon cross-sectionally throughout nursing education [ 6 , 24 , 107 ]. While legal regulations solely operate as a foundation for ethics education, Riedel et al [ 8 ] strongly suggested that the comprehensive development of ethical competence was a crucial step in the prevention and professional management of moral distress. Nevertheless, while building ethical competence is an important contribution to preventing and managing moral distress, a higher sensitivity for morally challenging situations simultaneously bears an increased risk for the experience of moral distress if it is impossible to relieve the experienced moral unease.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, moral decision-making is fundamental to the nursing profession as patient cases are becoming increasingly complex in the contemporary context of nursing [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. Simultaneously, in all of the three presented countries, the professional requirements and responsibilities of nurses are increasing.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations